(untitled) (Colombia Medica, 2024)
Introduction: Multicultural societies of the postmodern world are characterized by the complexity of their structure, organization, and operation. In such societies, there is a heterogeneous set of social players who experience a variety of phenomena in their daily lives in cities. Within this context, nursing care has developed and nurses in recent years have turned to ethnography as a tool in understanding socio-cultural reality and experience from the perspective of those living these experiences. This is a theoretical study seeking to reflect upon the application of an ethnographic approach in Brazilian nursing research in complex societies. Ethnography in Brazilian nursing research in complex societies: Brazilian nurses have appropriated the methodological tools and theories of nursing and anthropological studies to investigate the experiences and meanings attributed to health-disease process, cultural influence on health-related behaviors, as well as to evaluate and manage work processes. Further studies are emphasized to attempt to theorize and reflect upon the methodological construction of this research. This move highlights a shift in focus on nursing research and practice for a more integrative and complex view of human beings and reality. Ethnography helps us learn about a given reality and, as a result, we obtain new insights for understanding the phenomena. Reflection: It is considered that anthropological knowledge extends the nurses’ views on the subject about which they devote their practice, refining it. Being closer to the lives and experience of subjects, permits the perception of phenomena from the perspective of the players involved, offering professionals a different view on the needs and outcomes of nursing care.